How Does Timing Affect Trauma Treatment for Women Who Are Incarcerated? An Empirical Analysis - Bridges, Ana J. (Criminal justice and behavior, 2020)
Most women who are incarcerated have experienced sexual violence; difficulties adjusting to prison could interfere with women’s ability to benefit from trauma-focused therapy. Here, we explored whether therapeutic benefits of trauma treatment varied as a function of time since incarceration. Women (N = 128) participated in an 8-week group treatment for sexual violence victimization while incarcerated in a community corrections center for nonviolent offenses. Ninety participants consented to the study and completed self-report questionnaires assessing internalizing symptoms (depression, posttraumatic stress, and shame) before and after treatment. Bivariate correlations revealed a significant negative association between time since incarceration and pretreatment depression but not posttraumatic symptoms or shame. Dependent-sample t tests revealed significant improvements from pretreatment to posttreatment in internalizing symptoms. Longer time since incarceration did not significantly predict internalizing symptoms after controlling for pretreatment symptom severity. Findings suggest trauma-focused treatments can be offered to women shortly after they are incarcerated.